Penggunaan Modul Ajar pada Mata Pelajaran Pendidikan Agama Islam - Rahmawati, Indah Agustinah; Astutik, Anita Puji (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
This research was conducted to analyze the use of teaching modules in Islamic religious education subjects. The research method used is a qualitative method with a descriptive approach. Data collection techniques in this research include observation, interviews, questionnaires, and documentation. This research was conducted at SMP Muhammadiyah 5 Tulangan with the subjects being PAI teachers, students in class VIII-A, and class VIII-D. The results of the research conducted show that 90% of PAI teachers understand the use of teaching modules, while 10% of PAI teachers do not understand the use of teaching modules. The results of the class VIII student questionnaire showed that an average of 85% of students understood the teaching module, while 10% of students did not understand the teaching module. So it can be concluded that the use of teaching modules is very important for PAI teachers to apply to students according to the learning material. This is because the use of teaching modules can make it easier for students to understand learning material while also being able to improve student learning outcomes.